2017
DOI: 10.1111/cpf.12475
|View full text |Cite
|
Sign up to set email alerts
|

Effect of spontaneous saliva swallowing on short‐term heart rate variability (HRV) and reliability of HRV analysis

Abstract: The effects of effortful swallowing and solid meal ingestions on heart rate variability (HRV) have been examined previously. The effects of spontaneous saliva swallowing on short-term HRV and reliability of HRV analysis have not been studied before. The effect of saliva swallowing on HRV analyses parameters [meanRRI, SDNN (standard deviation of normal-to-normal), LF (low frequency), HF (high frequency) powers, LH/HF] and the reliability of LF and HF powers were investigated by frequency, time-frequency and int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 33 publications
2
6
0
Order By: Relevance
“…13 In another study, it was reported that the action of swallowing saliva was capable of modifying the HRV. 14 On the other hand, it has been reported that people with Sjögren's syndrome present a parasympathetic/sympathetic dysfunction, which agrees with a decrease in parasympathetic activity. 15,16 On the other hand, the RMSSD and pNN50 timedomain indices of the HRV are directly related to the parasympathetic activity rate of the ANS.…”
Section: Discussionmentioning
confidence: 89%
“…13 In another study, it was reported that the action of swallowing saliva was capable of modifying the HRV. 14 On the other hand, it has been reported that people with Sjögren's syndrome present a parasympathetic/sympathetic dysfunction, which agrees with a decrease in parasympathetic activity. 15,16 On the other hand, the RMSSD and pNN50 timedomain indices of the HRV are directly related to the parasympathetic activity rate of the ANS.…”
Section: Discussionmentioning
confidence: 89%
“…We found only four studies of the within-session reliability of HRV in short-term recordings in healthy adults [13][14][15][16]. These studies showed substantial relative reliability of HRV parameters [13][14][15][16], and low absolute reliability of HRV parameters [13,15,16]. The time domain parameters of HRV demonstrated greater reliability than the frequency domain parameters of HRV [13,15,16].…”
Section: Introductionmentioning
confidence: 84%
“…The literature search revealed that reports of the stability and reliability of HRV parameters over days/weeks/months far outweigh reports of the stability and reliability of HRV parameters obtained within a single resting session. We found only four studies of the within-session reliability of HRV in short-term recordings in healthy adults [13][14][15][16]. These studies showed substantial relative reliability of HRV parameters [13][14][15][16], and low absolute reliability of HRV parameters [13,15,16].…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…Of late, a study assessed cardiac autonomic regulation via heart rate (HR) variability (HRV) in healthy subjects throughout spontaneous swallowing 11 . The researchers revealed sudden distinct losses in the inter beat intervals (RR intervals) during the spontaneous swallowing stages.…”
mentioning
confidence: 99%